Benign solitary pulmonary necrotic nodules: How effectively does pathological examination explain the cause? - Ürer, Halide Nur; Günlüoğlu, Mehmet Zeki; Ünver, Nurcan; Toprak, Sezer; Gönenç Ortaköylü, Mediha (Hindawi Ltd, 2020)
Aims. We investigated the histopathological features of solitary pulmonary necrotic nodules (NNs) of undetermined cause. We combined our findings with those obtained using other methods to determine how well the etiological factors were explained.Methods. We screened patients who underwent surgery to treat solitary pulmonary granulomatous and nongranulomatous NNs of undetermined cause. The NN sizes and features of both the NNs and adjacent parenchyma were evaluated. Histochemical analyses included Ehrlich-Ziehl-Neelsen (EZN), Grocott, and Gram staining. Polymerase chain reaction (PCR) was used to detect tuberculous and nontuberculous mycobacteria, panfungal DNA,Nocardia,Francisella tularensistypes A and B, and actinomycetes.Results. The NNs were granulomatous in 78.9% and nongranulomatous in 21% of the 114 patients included. EZN staining or PCR was positive forMycobacteriumin 53.5% of all NNs: 62.2% of granulomatous and 20.8% of nongranulomatous NNs. We found a weak but significant correlation between granulomatous NNs andBacilluspositivity and a significant correlation between granulomas surrounding the NNs and the presence of multiple necroses. The NN etiology was determined via histopathological, histochemical, and PCR analyses in 57% of patients but remained undetermined in 42.9%.Conclusion. The causes of both granulomatous and nongranulomatous NNs can be determined by pathological examination. Granulomatous necrosis and granulomas in the adjacent parenchyma are important for differential diagnosis. When both features are present, they strongly support a diagnosis of tuberculosis, even in the absence of bacilli.
Keywords: Necrotic Nodules; Benign Solitary Pulmonary; Pathological Examination